(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Artificial intelligence (AI) has emerged as a transformative force capable of addressing pressing global challenges and driving positive change in industries. This abstract examines the role of AI in driving social welfare, highlighting its potential to address social issues and empower communities around the world. AI technologies including machine learning, natural language processing, and computer vision have provided innovative solutions in health, education, environmental sustainability, poverty reduction, and moreover AI-enabled diagnosis and predictive analytics in healthcare have improved patient outcomes by improving diagnosis and treatment plans. Filling in the blanks is a learning experience it is satisfied by needs. Furthermore, AI-driven industries help create environmental protection efforts through efficient resource management, ecosystem monitoring, and prediction of natural disasters in terms of social equity narratively, AI tools help reduce poverty, improve economic inclusion, and reduce bias in the decision-making process. However, the ethical implications of implementing AI require careful consideration. Issues of data privacy, algorithmic biases, and the ethical use of AI raise concerns that need to be addressed to ensure responsible and appropriate adoption of AI by government, organizations and communities intervening to establish regulatory frameworks and ethical guidelines to prioritize fairness, transparency and accountability in AI applications Business efforts are important.